The haunted school - Stine, R. L. (New York : Scholastic, 1997)
Things go from difficult to frightening for Tommy Frazer at his new middle school when he gets lost in a maze of empty classrooms and hears students crying for help behind the walls.
3.6
5-8
Keywords: Horror stories; Schools -- Fiction; Horror fiction; School stories